Basic documents on international law and the environment (Clarendon Press, 1995)
Basic Documents on International Law offers an authoritative and wide-ranging selection of key documents in this important and increasingly popular area of law and will provide students and scholars with an invaluable companion to the authors' highly successful textbook International Law and the Environment. The editors have compiled a collection which includes all the major treaties and other legal instruments relevant to the protection of the environment in international law. Topics covered include the codification and development of international environmental law, marine pollution, the protection of the atmosphere, nuclear risks, control of hazardous substances, and international watercourses.